2018
DOI: 10.1037/xlm0000433
|View full text |Cite
|
Sign up to set email alerts
|

What are the costs of degraded parafoveal previews during silent reading?

Abstract: It has been suggested that the preview benefit effect is actually a combination of preview benefit and preview costs. Marx et al. (2015) proposed that visually degrading the parafoveal preview reduces the costs associated with traditional parafoveal letter masks used in the boundary paradigm (Rayner, 1975), thus leading to a more neutral baseline. We report 2 experiments of skilled adults reading silently. In Experiment 1, we found no compelling evidence that degraded previews reduced processing costs associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 54 publications
11
28
2
Order By: Relevance
“…The reduction in preview costs in Experiments 1a-2a replicates Marx et al's (2015) original findings and provides further evidence that invalid masks may inflate the preview effect (Hutzler et al, 2019;Marx et al, 2016Marx et al, , 2017. Critically, however, the present data also demonstrate that the use of parafoveal degradation in such studies has the unintended consequence of adding additional costs due to the presence of highly distinct changes at the target word location (see Vasilev et al, 2018;Experiment 2). This may explain why some studies (Hutzler et al, 2019, Experiment 4;Vasilev et al, 2018, Experiment 1) have failed to replicate the decrease in preview costs on the target word that Marx et al (2015) originally reported.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The reduction in preview costs in Experiments 1a-2a replicates Marx et al's (2015) original findings and provides further evidence that invalid masks may inflate the preview effect (Hutzler et al, 2019;Marx et al, 2016Marx et al, , 2017. Critically, however, the present data also demonstrate that the use of parafoveal degradation in such studies has the unintended consequence of adding additional costs due to the presence of highly distinct changes at the target word location (see Vasilev et al, 2018;Experiment 2). This may explain why some studies (Hutzler et al, 2019, Experiment 4;Vasilev et al, 2018, Experiment 1) have failed to replicate the decrease in preview costs on the target word that Marx et al (2015) originally reported.…”
Section: Discussionsupporting
confidence: 84%
“…Critically, however, the present data also demonstrate that the use of parafoveal degradation in such studies has the unintended consequence of adding additional costs due to the presence of highly distinct changes at the target word location (see Vasilev et al, 2018;Experiment 2). This may explain why some studies (Hutzler et al, 2019, Experiment 4;Vasilev et al, 2018, Experiment 1) have failed to replicate the decrease in preview costs on the target word that Marx et al (2015) originally reported. In this sense, the present data show that the incremental boundary technique (Marx et al, 2015) can be a very useful tool for studying the preview costs associated with invalid masks.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…With the boundary paradigm, a lack of valid preview necessitates the presence of an invalid preview. Recent research indicates that "preview benefit" effects in such boundary paradigm studies are actually a complex mixture of valid preview benefits and invalid preview costs (Hutzler et al, 2013;Kliegl, Hohenstein, Yan, & McDonald 2013;Marx, Hawelka, Schuster, & Hutzler, 2015;Vasilev, Slattery, Kirkby, & Angele, 2018). Therefore, exploring how the absence of preview during return-sweeps influences lexical processing will also advance our understanding of "preview benefit" effects within the boundary paradigm.…”
Section: Lexical Influences and The Role Of Previewmentioning
confidence: 99%